"Mass-forming" Variant of Ischemic Colitis Is A Distinct Entity With Predilection for the Proximal Colon. (September 2015) - Khor, Tze S.; Lauwers, Gregory Y.; Odze, Robert D.; Srivastava, Amitabh
Abstract : We systematically evaluated the clinicopathologic features and outcome of a rare, unusual variant of ischemic colitis that presents as a mass lesion mimicking malignancy on imaging or colonoscopy. A retrospective search was performed for cases with a histologic diagnosis of ischemic colitis and a clinical impression of malignancy. Of the 23 patients initially identified, 4 were excluded because clinical and histologic review showed mucosal prolapse (n=1), discrete colon polyp (n=2), and a diverticular mass (n=1) without concern for malignancy. The mass-forming variant of ischemic colitis (n=19) was seen predominantly in elderly (mean age 71.8 y) women (63.2%) with a striking predilection for the right colon (13/19), particularly the cecum (n=6). Abdominal pain (52.6%) and hematochezia (26.3%) were the most common presenting symptoms. A computed tomography scan showed segmental thickening suspicious for malignancy in 6/8 patients. Colonoscopy revealed an exophytic (n=16) or stricturing (n=3) mass with a mean size of 4.67 cm. Mucosal biopsies showed features typical for ischemic colitis in all cases. A colectomy was performed in 4 cases. In 2, the mass-like appearance was due to marked submucosal and mural edema, whereas in the other 2 cases, with a malignant stricture-like lesion, marked submucosal fibrosis and cholesterol emboli were present. No malignancy was identified on follow-up in any patient (mean 39.9 mo). Follow-up colonoscopy was performed in 7 patients 1 to 32 weeks after initial presentation and showed resolution of the mass in all cases. Awareness of this rare variant of ischemic colitis will prevent unnecessary resections in these patients.